Análise do uso de escalas nas simulações de processos de estampagem - Silva, Peterson Silva da (2016)
The purpose of using software based on numerical approximations for metal forming is given by the need to ensure process efficiency in order to get high quality products at lowest cost and shortest time. This study uses the theory of similitude in order to develop a technique capable of simulating the stamping process of a metal sheet, obtaining results close to the real values, with shorter processing times. The results are obtained through simulations performed in the finite element software STAMPACK®. This software uses the explicit integration method in time, which is usually applied to solve nonlinear problems involving contact, such as the metal forming processes. The technique was developed from a stamping model of a square box, simulated with four different scale factors, two higher and two smaller than the real scale. The technique was validated with a bending model of a welded plate, which had a high simulation time. The application of the technique allowed over 50% of decrease in the time of simulation. The results for the application of the scale technique for forming plates were satisfactory, showing good quantitative results related to the decrease of the total time of simulation. Finally, it is noted that the decrease in simulation time is only possible with the use of two related scales, the geometric and kinematic scale. The kinematic scale factors should be used with caution, because the high speeds can cause dynamic problems and could influence the results of the simulations.